2010
DOI: 10.1016/j.artint.2010.08.002
|View full text |Cite
|
Sign up to set email alerts
|

When is it better not to look ahead?

Abstract: D.S. Nau), mitja.lustrek@ijs.si (M. Luštrek), ajpark2@super.org (A. Parker), bratko@fri.uni-lj.si (I. Bratko), Matjaz.Gams@ijs.si (M. Gams).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…We call these pathological situations local pathologies . As a consequence (and in accordance with the work of Nau et al), one can say that different games exhibit different degrees of local pathologies.…”
Section: Theoretical Analysissupporting
confidence: 83%
See 2 more Smart Citations
“…We call these pathological situations local pathologies . As a consequence (and in accordance with the work of Nau et al), one can say that different games exhibit different degrees of local pathologies.…”
Section: Theoretical Analysissupporting
confidence: 83%
“…Finally, a large experimental study was performed to examine the relationship between the degree of pathology in a game tree and the 3 prominent causes of pathology, namely, branching factor, local node similarity, and evaluation function granularity . In that study, the authors defined the degree of pathology for a search of depth d as the fraction of correct decisions made by searching to depth d over the fraction of correct decisions made by searching one level deeper.…”
Section: Background and Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a well-known fact arising in some bipersonal games is that of lookahead pathology, that is, that the deeper is the exploration performed (and hence the better is suppossedly the heuristic minimax value assigned to the position), the worse is the decision taken (Nau, 1982). Recently, the same phenomenon was described in one-agent real-time search (Lustrek & Bulitko, 2008;Nau, Lustrek, Parker, Bratko, & Gams, 2010).…”
Section: Introductionmentioning
confidence: 80%
“……" Many researchers have shown the importance of the lookahead depth for computer games, but none of them was related to checkers. Most of the findings are related to chess [14][15][16][17], where it was shown that increasing the depth level will produce superior chess players. However, Runarsson and Jonsson [18] showed that this was not the case for Othello, as they found that better playing strategies are found when TD learning when ε-greedy is applied with a lower look-ahead search depth and a deeper look-ahead search during game play.…”
Section: Introductionmentioning
confidence: 94%